THU0099 Monitoring of abatacept in rheumatoid arthritis patients with previous failure to biotherapies suggests that CTLA-4/CD3E and/or CD28/CTLA-4 MRNA ratio may predict response to treatment at 3 months. (23rd January 2014) - Eljaafari, A.; Tartelin, M.-L.; Aissaoui, H.; Miossec, P.
Abstract : Background: Abatacept is a human soluble recombinant fusion protein composed of the extracellular domain of cytotoxic T-lymphocyte antigen 4 (CTLA4) and the Fc domain of human IgG1. It targets T cell activation by inhibiting the interaction of CD28 with CD80-CD86 molecules. Objectives: To monitor and predict the efficacy of Abatacept treatment in rheumatoid arthritis (RA) patients with failure to biotherapies. Methods: 18 patients with failure to TNFa inhibitors or anti-CD20 mAb, were selected for treatment with Abatacept. DAS-28, ESR, and pain/joint scores were used to monitor the clinical response. Blood samples were collected at day 0 and at 1, 3, 6 and 12 months, using Paxgene tubes for mRNA analysis. PBMC were prepared by Ficoll gradient density. Samples were frozen, and thawed for longitudinal studies, either at 1 year treatment in responders, or before, if Abatacept had been stopped due to failure. mRNA expression was analyzed by qRT-PCR, using cyclophilin B (CPB) as a house keeping gene. Functional assays were performed using PHA as stimulus. Results were longitudinally analyzed and compared with those of healthy blood donor controls (HC). Results: Among the 18 patients included in the study, 50% remained on Abatacept at 1 year, whereas Abatacept was stopped at 3 to 6 months in the other 50% patients, due to clinical failure. Functional assays were performed in 6 patients (3 responders and 3 non responders). In the responders, T cell response to PHA was observed either from day 0, or upon time of treatment. In the 3 non responder patients, PHA did not induce any significant response at any time, unless anti-CD28 mAb was added. This led us to focus on Th-1, Th-2, Treg, Th-17, but also CD28, and CTLA-4 gene expression. Longitudinal qRT-PCR analysis of whole blood samples did not show any significant difference upon time, i.e: from day 0 to year 1, of Th- or Treg gene expression, in responders. However, a significant increase upon time of the CD3e/CPB mRNA ratio (p=0.0430), together with a statistical decrease in CD28/CD3e and CTLA-4/CD3e ratios (p=0.0399, 0.0004, respectively) was observed in responders, but not non responders. This resulted in a marked increase of the CD28/CTLA4 ratio (p=0.0448). Of particular interest is the analysis of these ratios at 1, 3 and 6 months, which demonstrated in responders, but not non responders, a significant decrease in the mRNA ratio of CTLA4/CD3e, in association with an increase of CD28/CTLA-4 (p=0.022, and 0.0098, respectively). Finally, the mRNA ratios at day 0 of CD28/CD3e and CTLA-4/CD3e were found to be significantly increased in RA patients, as compared with HC (p=0.0040, and 0.0003, respectively), supporting thus an abnormal regulation of these genes in RA. Conclusions: Response to Abatacept was correlated with an increase at one year of the CD3/CPB, and a decrease of CD28/CD3e and CTLA-4/CD3e mRNA ratios. This resulted in an increase of the CD28/CTLA-4 mRNA ratios, which is likely to improve the ability of T cells to respond to Ag upon time, as opposed with the well known inhibitory effect of Abatacept on short-term T cell activation.Our results also showed that CTLA-4/CD3e and CD28/CTLA-4 mRNA ratios were either down-or up-regulated as soon as 3 months, respectively, which designates them as putative predictive markers of the response to Abatacept. Disclosure of Interest: A. Eljaafari: None Declared, M.-L. Tartelin: None Declared, H. Aissaoui: None Declared, P. Miossec Grant/Research support from: Bristol MyersSquibb support